Correlation between coordinated water content and proton conductivity in Ca–BTC-based metal–organic frameworks - Mallick, Arijit; Kundu, Tanay; Banerjee, Rahul (Chemical communications (Cambridge, England), 2012)
Proton conductivity of five Ca-based MOFs which depends on the amount of water molecules coordinated to the Ca-centres has been reported. These MOFs show high temperature proton conductivity due to the strong hydrogen bonding between the lattice and coordinated water molecules.